Place of Residence and Its Role in the Development of College Students - Skaggs, C. Thomas (Canadian Journal of Counselling and Psychotherapy, 1972)
The main concern of this paper is the influence of place of residence on the performance of behavior patterns which contribute to the individual answering questions about himself in terms of what he is and what is important about him (Erikson, 1959).Each place of residence is shown to have advantages and disadvantages for the developmental process. However, it must be emphasized that whether or not an aspect of residential environment is advantageous must be determined according to the needs and developmental level of each particular individual. For some students their developmental patterns can best be satisfied through the experiences allowed in a residence hall environment, while others may require the experiences to be had in off-campus housing.